The Influence of Learning Motivation, Learning Discipline, and Family Environment on Students' Academic Performance - Sari, Mila; Altin, Darus; Wibawa, Dian Prihardini (International Journal of Magistravitae Management, 2024)
This study is driven by the issue of suboptimal student academic performance, primarily due to students' limited ability to comprehend lessons effectively. The purpose of this study is to identify and analyze the influence of learning motivation, learning discipline, and the family environment on students' academic performance at State Junior High School 10 Pangkalpinang. This research is classified as descriptive research and utilizes a quantitative approach. The sample consisted of 184 respondents selected through the census sampling technique. Data were analyzed using the multiple linear regression analysis method. The results indicate that learning motivation, learning discipline, and the family environment each have a positive and significant effect on the academic performance of students at State Junior High School 10 Pangkalpinang. Furthermore, the simultaneous test results demonstrate that learning motivation, learning discipline, and the family environment collectively have a positive and significant impact on students' academic performance.